2019
DOI: 10.4174/astr.2019.97.6.302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and characteristics of left-sided gallbladder: case series study of 10 patients

Abstract: PurposeThe aims of this case series study were to review the 10 patients who were diagnosed with left-sided gallbladder and analyze their anatomic variations in the bile duct, portal vein, and hepatic vessels.MethodsIn this case series study, 10 patients with left-sided gallbladder were retrospectively analyzed at 2 tertiary referral centers between April 2004 and May 2019.ResultsMean age was 61.1 years; there were 7 women and 3 men. Ten patients underwent laparoscopic cholecystectomy for acute cholecystitis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…True LSGB is a rare anatomical anomaly with an incidence rate of 0.1–1.2% and a rate of 0.07–0.08% in patients undergoing cholecystectomy. It occurs more frequently in women than in men at a ratio of 5:1 [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…True LSGB is a rare anatomical anomaly with an incidence rate of 0.1–1.2% and a rate of 0.07–0.08% in patients undergoing cholecystectomy. It occurs more frequently in women than in men at a ratio of 5:1 [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . reported that the median surgery time is 50 min (range, 35–160 min), which is less than that indicated by Jung et al ., who reported an operation time of 103 min (range, 65–240 min) [ 2 , 4 , 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variations probably have considerable clinical implications in managing hepatic resection, including donor hepatectomy. 19 In recent years, the treatment approaches for managing choledocholithiasis in children have become more specific; however, no gold standard procedure is available yet. The endoscopic approach for managing biliary tract obstruction in medical centers performing ERCP is usually the first choice.…”
Section: Discussionmentioning
confidence: 99%
“…Increased size of the left portal vein and distribution of the left portal vein crossing over to the right side of the liver is the crucial common features of the left-sided gallbladder. These variations probably have considerable clinical implications in managing hepatic resection, including donor hepatectomy (17).…”
Section: Case Reportmentioning
confidence: 99%